Democratization Process in Indonesia - Suny, Ismail (UI Scholars Hub, 2005)
The political reformation in Indonesia in 1998 has led to the amendments of the 1945 Constitution of the Republic of Indonesia that had been continually carried out into four series from 1999 until 2002. Through the amandments, the Constitution had basically amended and changed the nature and structure of Indonesia’s states institutions as well as mechanism of relationship among the state institutions.